Kinship and Y-chromosome analysis of 7th century human remains: novel DNA extraction and typing procedure for ancient material - Vaněk, Daniel; Sasková-Přenosilová, Lenka; Koch, Hubert (Croatian medical journal, 2009)
AIM: To develop novel DNA extraction and typing procedure for DNA identification of the 7th century human remains, determine the familiar relationship between the individuals, estimate the Y-chromosome haplogroup, and compare the Y-chromosome haplotype with the contemporary populations. METHODS: DNA from preserved femur samples was extracted using the modified silica-based extraction technique. Polymerase chain reaction amplification was performed using human identification kits MiniFiler, Identifiler, and Y-filer and also laboratory-developed and validated Y-chromosome short tandem repeat (STR) pentaplexes with short amplicons. RESULTS: For 244A, 244B, 244C samples, full autosomal DNA profiles (15 STR markers and Amelogenin) and for 244D, 244E, 244F samples, MiniFiler profiles were produced. Y-chromosome haplotypes consisting of up to 24 STR markers were determined and used to predict the Y-chromosome haplogroups and compare the resulting haplotypes with the current population. Samples 244A, 244B, 244C, and 244D belong to Y-chromosome haplogroup R1b and the samples 244E and 244F to haplogroup G2a. Comparison of ancient haplotypes with the current population yielded numerous close matches with genetic distance below 2. CONCLUSION: Application of forensic genetics in archaeology enables retrieving new types of information and helps in data interpretation. The number of successfully typed autosomal and Y-STR loci from ancient specimens in this study is one of the largest published so far for aged samples.
Keywords: Genotype; Forensic Genetics; polymerázová řetězová reakce; soudní genetika; Polymerase Chain Reaction; DNA Fingerprinting; lidé; genotyp; DNA fingerprinting; Forensic Anthropology; Humans; geny vázané na chromozom Y; Male; Fossils; dějiny starověku; zkameněliny; Microsatellite Repeats; genetické markery; mužské pohlaví; soudní antropologie; mikrosatelitní repetice; Genes, Y-Linked; History, Ancient; Genetic Markers